Efforts to increase the use of HIV testing services: What interventions have worked in Thailand? - Chris Jenkins (2018)
© 2017, SEAMEO TROPMED Network. All rights reserved. We reviewed and analyzed published research concerning efforts to increase regular use of HIV testing services in Thailand. Separate studies suggested that the creation of participatory and creative online spaces for information sharing and promoting community-based testing positively influence levels of HIV testing, including repeat-testing in some cases. Population targeted approaches, using same-day rapid tests, and using diverse locations for testing (medical and non-medical) may improve rates of testing. Thailand shows an example of successful HIV management and reduction. The challenge is to continue towards zero new infections and end an epidemic that is increasingly associated among people with specific risk behaviors. These characteristics make Thailand a case study for consideration by other national HIV programs.